The Many Roles of Galectin-3, a Multifaceted Molecule, in Innate Immune Responses against Pathogens - Laura Díaz-Alvarez; Enrique Ortega (Hindawi Limited, 2017)
Galectins are a group of evolutionarily conserved proteins with the ability to bind β-galactosides through characteristic carbohydrate-recognition domains (CRD). Galectin-3 is structurally unique among all galectins as it contains a C-terminal CRD linked to an N-terminal protein-binding domain, being the only chimeric galectin. Galectin-3 participates in many functions, both intra- and extracellularly. Among them, a prominent role for Galectin-3 in inflammation has been recognized. Galectin-3 has also been shown to directly bind to pathogens and to have various effects on the functions of the cells of the innate immune system. Thanks to these two properties, Galectin-3 participates in several ways in the innate immune response against invading pathogens. Galectin-3 has been proposed to function not only as a pattern-recognition receptor (PRR) but also as a danger-associated molecular pattern (DAMP). In this review, we analyze the various roles that have been assigned to Galectin-3, both as a PRR and as a DAMP, in the context of immune responses against pathogenic microorganisms.